1986
DOI: 10.1152/ajpregu.1986.250.6.r1003
|View full text |Cite
|
Sign up to set email alerts
|

Control of food intake by fatty acid oxidation

Abstract: The role of fatty acid oxidation in the control of food intake was studied using mercaptoacetate (MA), an inhibitor of fatty acid oxidation. Food intake, plasma free fatty acids (FFA) and ketone bodies, and blood glucose were measured. Rats were fed either a low-fat (LF, 3.33% fat) or a medium-fat (MF, 18% fat) diet. At the onset of the dark phase of the lighting cycle, MA did not affect food intake in LF rats but increased it 74% in MF rats in comparison to control. Four hours after the injection the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 0 publications
8
108
0
Order By: Relevance
“…2DG administration increased food intake in OM rats on a high-fat diet. These results are similar to results from experiments with Sprague-Dawley rats (20,26). Carbohydrate and protein intakes were stimulated by MA in OM rats, but fat intake did not change.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2DG administration increased food intake in OM rats on a high-fat diet. These results are similar to results from experiments with Sprague-Dawley rats (20,26). Carbohydrate and protein intakes were stimulated by MA in OM rats, but fat intake did not change.…”
Section: Discussionsupporting
confidence: 88%
“…This may be especially evident for S5B rats maintained on a high-fat diet. Alternatively, S5B rats may be more sensitive to the increase in circulating plasma fatty acids that are apparent after MA treatment (20,22), and this, in turn, antagonizes MA-induced feeding. Indeed, lipid infu-sion into the circulation can block the feeding response to MA (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of a high-GI diet led to decreased hepatic fat oxidation and then increased food consumption resulting in an increase in body weight and fat (17,18). Obesity has a strong correlation with the metabolic syndrome consisted of hypertension, dyslipidemia, insulin resistance, and type 2 diabetes.…”
Section: Articlesmentioning
confidence: 99%
“…This prolonged hyperinsulinemia would have the effect of directing nutrients from oxidation to storage (6). In fact, some studies demonstrated that hyperinsulinemia due to ingestion Articles Visuthranukul et alof a high-GI diet led to decreased hepatic fat oxidation and then increased food consumption resulting in an increase in body weight and fat (17,18). Obesity has a strong correlation with the metabolic syndrome consisted of hypertension, dyslipidemia, insulin resistance, and type 2 diabetes.…”
mentioning
confidence: 99%